Using Story Mapping Technique To Enhance Senior High Schools' Students Reading Comprehension: Classroom Action Research - Rofiq, Ainur; Wahjuningsih, Eka; Andika Hudori, Rizki Febri (English Education Study Program, 2022)
This research was intended to enhance the senior high school students’ reading comprehension achievement by using Story Mapping Technique at SMA Muhammadiyah 3 Jember. The design of the research was Classroom Action Research with the research participants were the Grade XI IPS 3. The result of the reading comprehension test in cycle 1 showed that the average percentage of the student who achieved the rarget was higher than before. The results of reading test, there were 25 students (78.11%) achieved the success criteria and 7 students (21.89%) got ≤ 75. Thus, the use of story mapping technique could enhance the eleventh grade students’ reading comprehension achievement. It was suggested for the teachers to use Story Mapping Technique to enhance the sudents’ reading comprehension achievement in reading class. Keywords: Story Mapping Technique, Reading Comprehension, Classroom Action Research